Anti-Bacterial Power of The Pecut Kuda Plant (Stachytarpheta jamaicensis L.) Against Leaf Blight Bacteria (Xanthomonas oryzae) - Hidayati, Ernin; Diniati, Herild; Suripto, Suripto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Treating leaf blight in rice, which is caused by the bacterium Xanthomonas oryzae, using anti-bacterial agents from synthetic chemical compounds often causes environmental problems, so it is necessary to study the use of natural anti-bacterial agents. The pecut kuda plant (Stachytarpheta jamaicensis) has the potential to contain anti-bacterial properties because the leaves are often used by the public as a medicine to heal fresh wounds. This research aims to determine the anti-bacterial power of the S. jamaicensis plant against X. oryzae bacteria. S. jamaicensis leaves were extracted in stages using a series of successive solvents, namely hexane, DCM, and ethanol. Each fraction of S. jamaicensis leaf extract was tested for its inhibitory power against the growth of X. oryzae on MHA medium using the well method. The inhibitory variable observed was the diameter of the clear zone formed during 5 x 24 hours of incubation. The clear zone diameter data was analyzed to determine the inhibitory power. The results showed that each fraction of S. jamaicensis leaf extract had inhibitory power against X. oryzae. The S. jamaicensis plant can be developed as a source of natural anti-bacterial which are bacteriostatic, especially against X. oryzae.